2021
DOI: 10.1186/s43088-021-00127-6
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality of non-sterile pharmaceuticals in Egypt

Abstract: Background The context and purpose of the study are as follows: Drug-borne infections may arise from non-adherence to strict microbiological quality of pharmaceuticals products. Moreover, presence of exceeding levels of microorganisms in non-sterile pharmaceuticals may lead to change of their organoleptic characteristics and loss of effectiveness. The aim of the study is to evaluate the microbiological quality of commonly used non-sterile pharmaceuticals in Alexandria, Egypt. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…passed the European Pharmacopoeia “2010” specifications, a result that matches that of previous studies by Salem et al. (2021) [ 2 ] and Al−Kaf et al. (2015) [ 3 ].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…passed the European Pharmacopoeia “2010” specifications, a result that matches that of previous studies by Salem et al. (2021) [ 2 ] and Al−Kaf et al. (2015) [ 3 ].…”
Section: Discussionsupporting
confidence: 85%
“…(2021) of non-sterile pharmaceuticals in Egypt. The later study showed that 17.03% and 19.23% of samples exceeded the maximum acceptable limit of TAMC and TYMC, respectively [ 2 ]. Similarly, to the results in our study, the Egyptian study also confirmed oral products were free from E. coli [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-sterile pharmaceuticals are the products that may contain microorganisms within the limits of the type and concentration [2]. Usually, the oral medicines and topical medicines are non-sterile [7]. The acidity of the stomach may act as a barrier to ingested microorganisms in the oral route and inactivation of the biological activities of the microorganism occurs [8].…”
Section: Introductionmentioning
confidence: 99%